Pengembangan Podcast dengan Model Addie pada Materi Cerita Rakyat Sebagai Sumber Belajar Berbasis Audio - Zam Zam Jamaludin; Erwin Rahayu Saputra (UNDIKMA, 2021)
This study aims to produce a podcast as an audio-based learning resource and determine its feasibility. This research was conducted using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) on folklore material. In this study, data were collected through observation and interviews, questionnaires and tests, which were then analyzed by paired two-sample t-test. The results of the content expert's review stated that the podcast developed was appropriate. The results of the expert review of audio-based learning resources stated that it was very good, while the review of learning design experts stated that the podcast developed was in the good category. Student responses in field trials showed student responses to the product were very good, which was 92.11%. The results of the calculation of student achievement before and after using interactive multimedia based on the results of the t-test carried out gave the results of t-count = 0.001 (<a = 00.5). The average result of the posttest of students is 86.92, which is above the KKM value set at 75. This shows that the development of podcasts as an audio-based learning resource is feasible to use in the learning process for folklore material.